REFLECTION OF THE PROBLEM OF FORMING INTEREST IN CHEMISTRY, BASED ON THE IMPLEMENTATION IN TEACHING THE PRINCIPLE OF CONNECTION WITH LIFE IN THE METHODOLOGY OF TEACHING CHEMISTRY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Relevance of the topic: In recent years, interest in chemistry among university students has declined, despite the fact that modern people increasingly use chemical substances and products in their daily lives. At the same time, the number of hours allocated to chemistry study is decreasing, and the volume of material covered is increasing. A contradiction arises between the need for chemical knowledge for modern people and a lack of understanding of the practical significance of the material being studied. The contradiction that exists in the practice of teaching chemistry today between the increased theoretical level of study of the subject at the initial stage and the insufficient development of logical thinking skills is the reason for the sharp decline in student interest in the subject. Therefore, the need to develop a culture of using chemicals in students, elements of conscious and safe handling of these substances, environmental standards and rules of conduct in the created artificial environment is the main goal of chemistry. Developing students' interest in chemistry, their cognitive activity, independence, and curiosity based on the principle of connection with life in teaching is the most important task of the modern school. This issue receives considerable attention in methodological literature and the practice of modern universities. Throughout the history of chemistry teaching methods in our country, this topic has occupied varying places in the curriculum. For example, in the 1920s, connection to real life was the foundation of the subject, and at times, the study of chemistry was replaced by practical work.